Currículo de matemática da Educação de Jovens e Adultos: análise de prescrições na perspectiva cultural da matemática - Januario, Gilberto (2012)
Our study investigates Mathematics Curriculum prescribed for Youth and Adult Education. We selected the Proposed Curriculum for the EJA, second segment of the Elementary School, as an example of curriculum prescribed by electing Volume I (Introduction) and Volume 3 (Mathematics) to answer the questions: What characteristics are presented in the Proposed Curriculum for the Education of Young and Adults that allow the approach of the formal culture of the informal culture of mathematics? What characteristics enculturators this curriculum? What criteria have on the organization of content? What options have the choice of contexts? We develop a qualitative research approach, type documentary analysis. The theoretical framework of this study refers to authors such as Pacheco and Sacristán the resumption of episodes, appearance, development and multiplicity of meanings attributed to the term curriculum; also work on the mathematics curriculum, the cultural perspective of mathematics and curriculum enculturator, with reference to theoretical Bishop and D Ambrosio; and studies Pires and Skovsmose about the curriculum and criteria for the choice of the contexts of mathematics learning environments. Analysis of the Proposed Curriculum for the EJA, guided by categories that emerged from theoretical frameworks, there are explicit recommendations for and potentially promoting the alignment of formal culture of informal culture of mathematics, through suggestions and guidelines such as those that consider the knowledge acquired from social relations of youth and adults as a starting point for learning, that content is proposed to promote a network of relations and knowledge of other areas, enabling a plurality of meanings of the concepts and activities, which emphasize to work with projects and investigations for the student to solve the mathematical ideas; the contents emphasize different applications of mathematics and to prepare the student to build increasingly complex ideas, from simple situations, the learning environments are designed in paradigms and research exercises, there is balance between the environment, and between exercises and research and are used different coping strategies, and encouraging young adults to clarify, by means of different records, such as mobilizing their knowledge and with the teacher asmediates the action of learning